The Value of Health Insurance: A Household Job Search Approach - Gabriella Conti; Rita Ginja; Renata Narita (Institute of Labor Economics (IZA), 2018)
Do households value access to free health insurance when making labor supply decisions? We answer this question using the introduction of universal health insurance in Mexico, the Seguro Popular (SP), in 2002. The SP targeted individuals not covered by Social Security and broke the link between access to health care and job contract. We start by using the rollout of SP across municipalities in a differences-indifferences approach, and find an increase in informality of 4% among low-educated families with children. We then develop and estimate a household search model that incorporates the pre-reform valuation of formal sector amenities relative to the alternatives (informal sector and non-employment) and the value of SP. The estimated value of the health insurance coverage provided by SP is below the government's cost of the program, and the corresponding utility gain is, at most, 0.56 per each peso spent.
Keywords: J64; D10; I13; J46; 330; search; household behavior; health insurance; informality; unemployment